Students’ perspective on using AI DeepL Translate for improving English writing skills - Khalawatul Iman; Nurul Afidah; Ulfa Wulan Agustina; Yuyun Bahtiar (SCHOOLAR: Social and Literature Study in Education, 2026)
Writing is an activity where someone can express their ideas in writing. AI in education refers to the use of technology that can be utilized in education. One example is in the learning process, which can be interactive and innovative. This research is urgent given the importance of English language skills as a tool for international communication, especially in developing countries like Indonesia. The purpose of this study was to determine students' perspectives on the use of DeepL Translate in writing skills. In the context of language learning, artificial intelligence-based translation tools such as DeepL Translate are increasingly popular among students. This study used a mixed method, combining quantitative and qualitative approaches. Quantitative data were collected through questionnaires distributed to students, while qualitative data were obtained through in-depth interviews with several students who used DeepL Translate in the process of writing descriptive texts. The results showed that most students had a positive response to the use of DeepL Translate. They felt this tool helped them understand new vocabulary, improve sentence structure, and increase the accuracy of their writing. However, some students also expressed concerns about the dependence on this translation tool and its potential negative impact on their independent writing skills. These findings provide important insights for teachers in understanding how technology can be utilized to support writing skills learning, as well as the challenges students face in using it.